Endometriosis. Surgical treatment. - Romero Oliva, Felipe (2015)
Simply diseases pelvic cavity is so compromised the ability, judgment and experience of the gynecologist, as compared to surgical treatment of endometriosis. The required security of functioning ovarian tissue, both for the maintenance of the female reproductive activity to the symptomatology of the disease, many times requires the expert to have to take the decision whether to keep severe ovarian function or destroy the benefit of the patient.